Rogowski coil sensor in the digitization process to detect partial discharge - Eka Putra Waldi; Asri Indah Lestari; Rudy Fernandez; Syaifa Mulyadi; Yoshinobu Murakami; Naohiro Hozumi (Universitas Ahmad Dahlan, 2020)
This paper presents the construction of a Rogowski Coil sensor with an air core to detect partial discharge using a digital oscilloscope. Two types of sensors are used. The first is the primary sensor winding with back wire, and the second is without back wire, labeled BW and WBW, respectively. The numbers of primary-turn in the sensors are 5, 10, 20, and 40 turns. The performance of the sensors is tested using two types of tests. First, the wave response test with a fixed imitation partial discharge magnitude input is used to select the optimum sensitivity with the lower sampling rate, aims to select the peak or valley value as a magnitude partial discharge value. The second test is using an imitation partial discharge ramp to check the linearity of the sensors. The imitation of the partial discharge inputs is generated by a commercial charge calibrator. The wave response test results show an increase in the number of turns that corresponds to an increase of the sensor output for both sensors in a non-linear trend. In determining the sampling rate, the detection of magnitude in the valley is better than the peak. All sensors act linear toward the imitation partial discharge ramp either in BW or WBW conditions.